2011
DOI: 10.1158/1538-7445.am2011-2412
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2412: Molecular characterization of hepatocellular carcinoma (HCC) patient-derived explant models

Abstract: Recent evidence suggested that cancer patient-derived explant mouse models can maintain certain pathological and molecular features of the original diseases/patients, which offers potential opportunities for testing “personalized medicine” preclinically. We have established over 20 HCC explant models by directly implanting fresh tumor tissues derived from HCC patients into immunodeficient mice. To assess whether these HCC models would represent HCC clinical characteristics and individual patient diversity, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The analyses of gene copy number, gene mutation, mRNA expression, and protein expression profiles demonstrated that transplanted tumors preserve the genotypic alterations of the original tumors. Consistent with the concept of oncogene addiction and tumor suppressor hypersensitivity, amplification of MYC and cyclin D1 oncogenes and deletion of DLC1 and FHIT TSGs were detected in different individual models, as well as in corresponding patients’ HCC tissues (149). …”
Section: Modulation Of Dlc1 and Myc In Hepatocellular Carcinoma: Prossupporting
confidence: 72%
“…The analyses of gene copy number, gene mutation, mRNA expression, and protein expression profiles demonstrated that transplanted tumors preserve the genotypic alterations of the original tumors. Consistent with the concept of oncogene addiction and tumor suppressor hypersensitivity, amplification of MYC and cyclin D1 oncogenes and deletion of DLC1 and FHIT TSGs were detected in different individual models, as well as in corresponding patients’ HCC tissues (149). …”
Section: Modulation Of Dlc1 and Myc In Hepatocellular Carcinoma: Prossupporting
confidence: 72%